Hybrid Layer-by-Layer Film of Polyelectrolytes-Embedded Catalytic CoFe2O4 Nanocrystals as Sensing Units in Capacitive Electrolyte-Insulator-Semiconductor Devices - Morais, Paulo V. [UNESP]; Silva, Anielle C. A.; Dantas, Noelio O.; Schöning, Michael J.; Siqueira, José R. (Wiley, 2019)
Nanostructured materials have exhibited great potential applications in the field of (bio)sensing. In particular, the capacitive electrolyte-insulator-semiconductor (EIS) sensor is a suitable field-effect device for integration of film-based nanostructures as sensing units. In this study, the fabrication of a hybrid nanostructured film using the layer-by-layer (LbL) technique combining cobalt ferrite (CoFe2O4) nanocrystals complexed with poly(vinylpyrrolidone) (PVP) and embedded with a poly(amidoamine) (PAMAM) dendrimer is investigated. LbL films containing a PAMAM/PVP-CoFe2O4 architecture with different bilayers are fabricated onto EIS chips of Al/p-Si/SiO2. The morphology of the films is characterized by atomic force microscopy (AFM) and the sensing properties toward H2O2 detection are evaluated by capacitance–voltage (C/V) and constant capacitance (ConCap) measurements. By correlating the electrochemical and morphological properties of the films, the findings lead to an optimized system, in which the best performance is observed for a 3-bilayer EIS-(PAMAM/PVP-CoFe2O4) sensor, exhibiting a sensitivity of ca. 26.5 mV decade−1 and limit of detection of ca. 157 × 10–6 m toward H2O2. The set-up presents for the first time a field-effect sensor for H2O2 detection as an alternative to conventional amperometric H2O2 sensors.
Keywords: CoFe2O4 nanocrystals; EIS sensors; H2O2 detection; layer-by-layer films